2018
DOI: 10.1667/rr15059.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in the Response to Normal Tissue Radiation Injury

Abstract: The transcription factor Nrf2 is an important modulator of antioxidant and drug metabolism, carbohydrate and lipid metabolism, as well as heme and iron metabolism. Regulation of Nrf2 expression occurs transcriptionally and post-transcriptionally. Post-transcriptional regulation entails ubiquitination followed by proteasome-dependent degradation. Additionally, Nrf2-mediated gene expression is subject to negative regulation by ATF3, Bach1 and cMyc. Nrf2-mediated gene expression is an important regulator of a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 94 publications
1
32
0
Order By: Relevance
“…LCE s, SPRP , KRT ) [ 15 , [23] , [24] , [25] , [26] , 28 , 30 , 31 ]. Strikingly, NRF2 activation also occurs in response to exposure to IR, consistent with the crucial involvement of free radical/ROS formation in driving the oxidative and genotoxic stress that underlies IR-mediated tissue damage [ [32] , [33] , [34] , [35] , [36] , [37] ]. Therefore, we tested the feasibility of NRF2 activation for skin radioprotection in a preclinical model, with the ultimate goal of translating said findings to benefit cancer patients receiving RT.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…LCE s, SPRP , KRT ) [ 15 , [23] , [24] , [25] , [26] , 28 , 30 , 31 ]. Strikingly, NRF2 activation also occurs in response to exposure to IR, consistent with the crucial involvement of free radical/ROS formation in driving the oxidative and genotoxic stress that underlies IR-mediated tissue damage [ [32] , [33] , [34] , [35] , [36] , [37] ]. Therefore, we tested the feasibility of NRF2 activation for skin radioprotection in a preclinical model, with the ultimate goal of translating said findings to benefit cancer patients receiving RT.…”
Section: Introductionmentioning
confidence: 65%
“…The concept of NRF2-directed topical radioprotection and prevention of radiation-induced dermatitis has remained largely unexplored [ 1 , [33] , [34] , [35] , [36] , [37] , [48] , [49] , [50] ]. Herein, we have elucidated the critical role that NRF2 plays in mitigating IR-induced damage and tested the efficacy of topical application of bixin to negate the effects of RT in non-tumor tissue, specifically radiation-induced dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…PBI‐BM5‐induced oxidative stress was associated with modulation of Nrf2 and antioxidant gene expression. NRF2 is a transcription factor critical for the expression of antioxidant genes 50,51 . Immunofluorescence imaging, immunoblot analysis, and Nrf2 mRNA measurement by RT‐qPCR indicated that PBI‐BM5 caused a significant reduction of Nrf2 expression, which was prevented by RP1 at 24 hours post‐irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…They found that MyD88 was instrumental for regulating inflammatory processes that aid in recovery from radiation [ 55 , 64 ]. The activation of cGMP–AMP synthase–stimulator of interferon genes (cGAS-STING) signaling and ROS/RNS also plays an important role in lung injury mediated by non-infectious inflammatory processes [ 65 , 66 ]. The major signaling pathways involved in immunotherapy-induced RRP are shown in Fig.…”
Section: Main Textmentioning
confidence: 99%